The Lviv School of Philosophy in the Development of Educational Sciences (1914-1939). Contributors, Achievements, Continuations - Kazimierz Szmyd (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The article is an attempt to comprehensively search the development of academic pedagogical thought and educational practice at the University of Lviv at the end of the 19th century, at the beginning of the 20th century and in the period of the Second Republic of Poland. The intention of the author was determining mental sources and academic conditionings of being born new theoretical concepts of educational sciences and their application in educational and pedagogical practice at the University of Lviv and in its intellectual proximity. Attention was paid to the origin and symptoms of scientification, processes of rationalizing pedagogical thinking, searching for its basis within the circle of philosophy, culture and society sciences, but first of all in psychological knowledge about a human being. It came a long way from philosophy and speculative psychology to empirical and humanistic psychology, which allowed to intensify the main phases and formations of educational sciences in Lviv in their historical and qualitative development. A crucial role of Kazimierz Twardowski was highlighted with his Philosophical School, changes of philosophy itself and methods of its practicing, and especially the process of emerging professional philosophy and autonomy of pedagogy as a science and academic discipline. Attention was paid to - meaningful in Lviv - a process of creating psychology and pedagogy on the basis of philosophical anthropology, socio-cultural axiology and knowledge of human development in non-biological contexts. The processes were shown in a convention of a biographic and scientific analysis of achievements of the most prominent representatives of educational sciences in Lviv. Through searching for provenance, influences and distinctiveness of the individual way of Lviv psychologists and educationists connected with the Lviv school of philosophy. These origins determined a kind of authorization of pedagogy based on philosophy of human, his culture and social life realities, on the borderlands of people and culture in the contemporary Galicia.